2010
DOI: 10.1186/1471-244x-10-101
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific profiles of tobacco use among non-institutionalized people with serious mental illness

Abstract: BackgroundIn many countries, smoking remains the leading preventable cause of death. In North America, reductions in population smoking levels are stabilising and, in recent years, those involved in tobacco control programming have turned their attention to particular segments of society that are at greatest risk for tobacco use. One such group is people with mental illness. A picture of tobacco use patterns among those with mental illness is beginning to emerge; however, there are several unanswered questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 41 publications
(45 reference statements)
6
33
3
4
Order By: Relevance
“…In addition, the relatively high price of cigarettes in Brazil, considered the highest in the world, may also have contributed to this reduction 30 . Our results are corroborated by the findings of studies in high income countries that observed a higher rate of current smoking prevalence among patients with mental illnesses than in the general population 5,6,7 . However, it is important to note that the psychiatric patients from our sample did not start smoking earlier (mean age = 16 years) than the general population (13 to 15 years of age) 29 .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In addition, the relatively high price of cigarettes in Brazil, considered the highest in the world, may also have contributed to this reduction 30 . Our results are corroborated by the findings of studies in high income countries that observed a higher rate of current smoking prevalence among patients with mental illnesses than in the general population 5,6,7 . However, it is important to note that the psychiatric patients from our sample did not start smoking earlier (mean age = 16 years) than the general population (13 to 15 years of age) 29 .…”
Section: Discussionsupporting
confidence: 82%
“…As in other studies, an association was found between current smoking and several sociodemographic characteristics, including being male, older age, low education level 6,11,13,14,16 , and history of homelessness 40,41 , while a negative association was found between smoking and practicing a religion 42,43 . A low level of education may be considered a marker for low access to knowledge and understanding of the harmful effects of tobacco 16 .…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations